The radiation effect of ion species on the microstructure of nanoporous gold. (1st January 2021) - Hu, Z.Y.; Xu, C.; Liang, Y.X.; Yan, Y.; Yang, K.J.; Liu, Z.L.; Wang, X.J.; Fu, E.G.
Abstract: Gold (Au) and carbon (C) ion irradiations were performed on nanoporous gold (NPG) leaves to study the radiation impact of ion species on the microstructure of NPG from the aspects of ligament size, surface areal porosity, ligament surface and internal defect clusters. The results show a great dependence on the species of incident ions when NPG is subjected to the deliberately designed similar radiation exposures of ion irradiations. Heavier ions (Au) are more efficient in changing the surface morphologies of ligaments while lighter ions (C) tend to cause more obvious coarsening of ligaments. The difference is mainly originated from the collision cascade size and the deposited energy density induced by different kinds of incident ions. The present study may help better understand the radiation response mechanism of NPG under different irradiation environments. Graphical abstract: Image, graphical abstract